Diverse Magmatic Evolutionary Trends of the Northern Andes Unraveled by Paleocene to Early Eocene Detrital Zircon Geochemistry. (12th September 2022) - Jaramillo, Juan S.; Zapata, Sebastian; Carvalho, Monica; Cardona, Agustin; Jaramillo, Carlos; Crowley, James L.; Bayona, Germán; Caballero‐Rodriguez, Dayenari
Abstract: The Paleocene‐early Eocene continental magmatic arc (PECMA) in the Northern Andes is an example of arc magmatism following a major collisional event. This arc formed after the arc‐continent collision between the Caribbean Plate and the South American continental margin at ca. 72 Ma. We used detrital zircon LA‐ICP‐MS and CA‐ID‐TIMS geochronology and geochemistry to complement the limited plutonic record of the PECMA and better characterize the PECMA's magmatic evolution. Zircon geochronology and their respective trace element geochemistry were analyzed from Paleocene‐early Eocene strata of the Bogotá Formation in the foreland region. Our results show that after the collision of the Caribbean Plate, the magmas in the PECMA differentiated under a thick continental crust with limited subduction input at ca. 66 Ma. By 62–50 Ma, scattered patterns of Hf, U, U/Yb, and Yb/Gd ratios in detrital zircons suggest the existence of contrasting magmatic inputs attributed to different depths of crustal fractionation, varied temperatures of crystallization, and significant mantle and subduction inputs. These diverse magmatic patterns reflect the evolution of the continental crust. We proposed that oblique convergence and strike‐slip tectonics favored contrasting crustal architectures along the continental margin while local lithosphere dripping from a previously thickened crust promoted the formation of hot magmas under a thick continental crust. Key Points: Detrital zircon geochemistry was used to better refine the post‐collisional Paleocene to Eocene tectono‐magmatic evolution of the Northern Andes The Paleocene‐early Eocene detrital zircons crystallized in contrasting magmatic conditions and under varying crustal thicknesses Strike‐slip tectonics, crustal dripping, and a previously thickened continental crust can explain the observed diverse magmatic trends